2022
DOI: 10.3389/fphar.2021.813587
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Regular Use of Gastric Acid Suppressants and Subsequent Risk of Cholelithiasis: A Prospective Cohort Study of 0.47 Million Participants

Abstract: Background: Gastric acid suppressants have a major impact on gut microbiome which in turn, may increase the risk of cholelithiasis, but epidemiological evidence remains unclear. We undertook this research to evaluate the association between regular use of proton pump inhibitors (PPIs) and H2-receptor antagonists (H2RAs) with risk of cholelithiasis.Methods: Prospective cohort study included 477,293 UK residents aged 37–73 years from the UK Biobank. We included the participants reported PPI or H2RA use, and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…However, a few reports suggest that proton pump inhibitors could increase gallstone disease risk. In a recent large prospective study using UK Biobank data, regular use of proton pump inhibitors and H2-receptor antagonists was associated with increased risk of gallstones 28. Associations of proton pump inhibitor use have also been reported with cholangitis,29 cholecystitis,30 and bile duct cancer 31,32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few reports suggest that proton pump inhibitors could increase gallstone disease risk. In a recent large prospective study using UK Biobank data, regular use of proton pump inhibitors and H2-receptor antagonists was associated with increased risk of gallstones 28. Associations of proton pump inhibitor use have also been reported with cholangitis,29 cholecystitis,30 and bile duct cancer 31,32.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent large prospective study using UK Biobank data, regular use of proton pump inhibitors and H2-receptor antagonists was associated with increased risk of gallstones. [28] Associations of proton pump inhibitor use have also been reported with cholangitis, [29] cholecystitis, [30] and bile duct cancer. [31,32] Possible mechanisms of gastric acid suppressants include decreased gallbladder motility leading to delayed gallbladder emptying, bile duct morphological changes, and gut microbiome imbalance and its effects on bile acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…At baseline, regular use of PPI was first recorded using an electronic questionnaire and then confirmed by a United Kingdom Biobank nurse ( Yang et al, 2021 ; Yang et al, 2021 ; Xia et al, 2021 ). The recorded type of PPIs included omeprazole, lansoprazole, pantoprazole, rabeprazole, and esomeprazole.…”
Section: Methodsmentioning
confidence: 99%
“…The two are connected through the duodenum and blood, and colonizing the biliary tract is not difficult for intestinal bacteria. Another recent prospective cohort study based on 470,000 participants demonstrated an association between an increased risk of gallstones and disturbances in the gut microbiota caused by the use of stomach acid inhibitors ( 86 ). A team found that the intestinal microbiota of mice with gallstones is seriously disordered and identified 33 gallstone markers at the phylum, class, order, family, and genus levels.…”
Section: Gut Microbiota and Gallbladder Principal Diseasesmentioning
confidence: 99%